1999
DOI: 10.1038/sj.ejcn.1600774
|View full text |Cite
|
Sign up to set email alerts
|

The quantitation of lipoprotein lipase mRNA in biopsies of human adipose tissue, using the polymerase chain reaction, and the effect of increased consumption of n-3 polyunsaturated fatty acids

Abstract: Objective: To examine the effects of the consumption of ®sh oils on the gene expression of lipoprotein lipase (LPL, EC 3.1.1.34) in human adipose tissue. In order to measure LPL mRNA in adipose tissue samples obtained by needle biopsy from human volunteers a competitive, reverse transcriptase PCR (RT-PCR) protocol was developed. Design: A randomised controlled, single blind cross over dietary study which compared the effects of a low level n-3 polyunsaturated fatty acids (PUFA) using normal foods enriched with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This study set out to substantiate earlier findings from our laboratory that showed positive effects of fish oil on the pre-translational regulation of LPL gene expression in the epididymal fatpads of rats (12). In a follow-up study on a small group of normal, healthy male subjects (n ϭ 6), the level of AT-LPL mRNA was shown to increase in four out of six subjects in response to fish oil (13). Furthermore, changes in the level of AT-LPL mRNA were inversely associated with changes in fasting plasma TG and postprandial lipemia (AUC), suggesting that LPL gene expression may control longer-term changes in the handling of exogenous and endogenous TG.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study set out to substantiate earlier findings from our laboratory that showed positive effects of fish oil on the pre-translational regulation of LPL gene expression in the epididymal fatpads of rats (12). In a follow-up study on a small group of normal, healthy male subjects (n ϭ 6), the level of AT-LPL mRNA was shown to increase in four out of six subjects in response to fish oil (13). Furthermore, changes in the level of AT-LPL mRNA were inversely associated with changes in fasting plasma TG and postprandial lipemia (AUC), suggesting that LPL gene expression may control longer-term changes in the handling of exogenous and endogenous TG.…”
Section: Discussionsupporting
confidence: 80%
“…This was performed using the multi-specific internal standard or competitor, published by Laville et al (19), kindly donated by Professor Hubert Vidal. The production of this competitor from the vector has been previously described by Murphy et al (13). RT-PCR utilized oligonucleotide primers that amplify both the competitor and the target RNA in the same reaction, producing cDNA products of different sizes, 267 bp and 227 bp, respectively.…”
Section: Assay Of Lpl Mrna Levelsmentioning
confidence: 99%
“…1c) and of CD36, the major FA membrane transporter [106, 107]. Similarly, although FO upregulates postprandial LpL expression in human adipose tissue [108], suggestive of increased FA uptake by adipose, no effect on body weight has been seen in multiple studies. Indeed, a few small clinical trials have reported weight loss [109-111].…”
Section: Tissue Specific Effects Of Fo and The Regulation Of Tg Anmentioning
confidence: 99%
“…This reduction has been observed in patients consuming a LC n-3 PUFA-rich meal when compared with those receiving a saturated fatty acid-rich meal (Zampelas et al 1994). Murphy et al (1999) investigated the effects of fish oil on gene expression of LPL in human adipose tissue, and reported increased LPL mRNA expression following consumption of a LC n-3 PUFA-enriched diet when compared with a non-enriched diet. Increased fatty acid oxidation and reduced fatty acid synthesis decrease fatty acid availability for TAG synthesis and incorporation into lipoproteins, while increased LPL activity in response to fish oil treatment may accelerate clearance of TAG from the circulation (Weber & Raederstorff, 2000).…”
Section: Pufa and Insulin Actionmentioning
confidence: 99%